Neuroimmunity in amyotrophic lateral sclerosis: focus on microglia. Issue 3 (2nd April 2020) - Motataianu, Anca; Barcutean, Laura; Balasa, Rodica
Abstract: Amyotrophic lateral sclerosis (ALS), an incurable, devastating condition of the central nervous system, is characterized by selective destruction of motoneurons with an important contribution of innate and adaptative immunity. Microglia and immune cells are key players in neuroinflammation and active participants in ALS pathogenesis. Recent experiments in animal models have shown that microglia display both neuroprotective and neurotoxic properties, depending on the stage of disease progression and cytokine secretion. A better knowledge of the interactions between T cells and microglia in the immunopathogenesis of ALS is desirable for the development of ALS therapeutic strategies.